2020
DOI: 10.5937/tehnika2002161s
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid model for uncertainty assessment in open pit optimization

Abstract: Today deposits are often, small in size, with poor quality and with complex structure and geometry, which makes them very difficult to mine. For this reasons, taking into account a wide range of parameters is the most important thing for the successful managing of the economically viable project. The problem is that practically, value of every parameter is strongly connected with many uncertainties. That's why, all uncertainties should be incorporated in calculations in order to provide more realistic solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Mining projects are risky because of the uncertain nature of mineral deposits (Park and Nelson 2013; Wardhani 2015; Dow 2019). Stevanović et al (2020) showed that realistic and robust solutions should incorporate all sources of uncertainty in calculations and assess their impact on the project's success before deciding on an investment. Mining investment requires significant capital expenditure, considering the technical, economic, and market conditions with relatively long payback periods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mining projects are risky because of the uncertain nature of mineral deposits (Park and Nelson 2013; Wardhani 2015; Dow 2019). Stevanović et al (2020) showed that realistic and robust solutions should incorporate all sources of uncertainty in calculations and assess their impact on the project's success before deciding on an investment. Mining investment requires significant capital expenditure, considering the technical, economic, and market conditions with relatively long payback periods.…”
Section: Introductionmentioning
confidence: 99%
“…Risk analysis is an effective tool that helps decision-makers recognize and manage the dynamic and uncertain environment in which the mining industry operates (Kroese et al 2014; Foo 2015; Foo et al 2018). The optimization goal of a mining project is to maximize the NPV mean value and reduce the NPVaR (Beck 2013; Ampofo 2017; Franco-Sepulveda et al 2017; Stevanović et al 2020). Conventional NPV models assume that the value of each input parameter adopted as a unique correct value fixes all future outcomes.…”
Section: Introductionmentioning
confidence: 99%